Electrochemical Method for the Assay of Organic Peroxides Directly in Acetonitrile - Vanina Ivanova; Mariya Pimpilova; Maria Stoyanova; Nina Dimcheva (Molecules)
Lipid peroxidation is a major process that determines the quality of various oil samples during their use and storage, in which the primary products are hydroperoxides (HP’S). HP’S are very stable compounds at ambient conditions and are harmful to human health. Therefore, the evaluation of the degree of oil oxidation is an excellent tool for ensuring food safety. The peroxide value (PV) is the main parameter used for quality control in oils. Herein, we propose an alternative electrochemical method to the classical iodometric titration method most widely used for determining the PV. Our approach is based on the electrochemical quantification of hydroperoxides/peroxides in an organic solvent medium (acetonitrile and organic ammonium salt) using a composite electrocatalyst–glassy carbon electrode modified with 2D-nanomaterial graphitic carbon nitride doped with Co3O4. Calibration was made by the method of standard addition using benzoyl peroxide (BPO) as a model peroxide compound, dissolved in chloroform and added to fresh Rivana-branded anti-cellulite oil, used as a model oil sample. Calibration plots showed a linear response and the very good reproducibility of the analytical result (R2 ˃ 0.99). Further, in terms of accuracy, the method showed good results, since the BPO quantitative analysis was close to the theoretical response. In addition, the accuracy of the electrochemical method was compared with that of the standard iodometric titration method for determining the PV of vegetable fats (according to a standard method). Finally, using the electrochemical method, the concentration of peroxides was determined in a real sample—an anti-cellulite oil of the trademark Rivana with an expired shelf life.